The implementation of Green Innovation and Environmental Management Accounting and Impact on Firm Profitability - Putra, Pasca Dwi; Harahap, Khairunnisa; Agusti, Ivo Selvia; Zainal, Andri; Thohiri, Roza (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2023)
Businesses compete for green innovations that boost profitability while reducing their environmental footprint. The purpose of this study is to determine the impact of green-based innovation and environmental management accounting on the profitability of companies, as measured by the return on assets. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in the observation year 2021. The hypothesis is tested using multiple linear regression. Findings show that green innovation and environmental management accounting can increase firm profitability. The implications of the results of this study show the importance of green innovation and environmental management accounting in enhancing firm profitability.